2017
DOI: 10.1080/21691401.2017.1360326
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of amino-modified chiral mesoporous silica nanoparticles in delivering indometacin

Abstract: The present study established indometacin (IMC) delivery system with chiral mesoporous silica nanoparticles (CMSNs) and amino-modified chiral mesoporous silica nanoparticles (Amino-CMSNs) that previously reported as pharmaceutical excipients, and their systemic biological effects, mainly consisting of in vitro drug intestinal permeability, haemolysis assay, in vivo pharmacokinetics, anti-inflammation pharmacodynamics and gastric irritation, were addressed. It turned out that the two IMC delivery systems establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Pahweenvaj Ratnatilaka Na Bhuket designed a prodrug for curcumin to improve its solubility and oral bioavailability [16]. Li et al found that amino-modified chiral mesoporous silica nanoparticles exhibited improved drug dissolution and reduced hemolysis, which subsequently increased bioavailability [17]. It is therefore of great importance to develop various approaches to improve the water-solubility of BCS II drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Pahweenvaj Ratnatilaka Na Bhuket designed a prodrug for curcumin to improve its solubility and oral bioavailability [16]. Li et al found that amino-modified chiral mesoporous silica nanoparticles exhibited improved drug dissolution and reduced hemolysis, which subsequently increased bioavailability [17]. It is therefore of great importance to develop various approaches to improve the water-solubility of BCS II drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Other than these two factors, we also could not dismiss the effects of other physicochemical properties of nanoparticles such as particle shape 23,24 and stiffness. 25 The use of aminofunctionalized silica nanoparticles as drug nanocarriers offers some advantages such as neglectable cytotoxicity, 10 safe for circulation in blood, 26 higher dissolution rate and bioavailability, 26 and improved thermal stability. 27 To study how functionalized silica nanoparticles internalized into cells, we also treated cells with endocytosis inhibitors such as Amiloride-HCl or Amantadine-HCl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These porous materials This journal is © The Royal Society of Chemistry 2023 are widely used in biosensors and drug delivery systems because of their large pore size, high surface area, tunable pore shape, flexible modification of the inner and outer surfaces, and relatively good thermal stability. [38][39][40][41][42][43] The large specific surface area and pore volume of MSNs can provide space for the adsorption or storage of biomolecules such as GOx. In addition, the inner and outer surfaces of MSNs can be modified with simple groups to enable complex functionalization of the material.…”
Section: Mesoporous Silica Nanocompositementioning
confidence: 99%